De beste de baas? Verdienste, respect en solidariteit in een meritocratie - Tonkens, Evelien; Swierstra, Tsjalling (Studies over politieke vernieuwing, 2008)
It is generally thought that all people should have equal opportunities and their social position should not be dictated by race, sex or heritage. This ideology of meritocracy has been embraced by the Dutch and other European societies. But is this something to strive for? This provocative book has a number of renowned philosophers and sociologists look at the downside of meritocracy. They show that meritocracy runs counter to other important ideals such as solidarity, respect and democracy.